Trends in cholesterol testing during the COVID-19 pandemic - Esra D. Gumuser; Sara Haidermota; Phoebe Finneran; Pradeep Natarajan; Michael C. Honigberg (Elsevier, 2021)
Objective: To characterize trends in cholesterol testing since the start of the COVID-19 pandemic. Methods: We extracted testing for total cholesterol performed in adults ≥40 years old within the Mass General Brigham healthcare system between March and September 2020, as well those performed between March and September 2019 (reference period). Weekly cholesterol testing rates during the 2020 vs. 2019 study periods were compared using the paired samples t-test. Secondary analyses compared testing volumes and patient characteristics during the first vs. second half of the 2020 study period. Results: The study sample included 296,599 tests for total cholesterol performed in 220,215 individuals. The mean (SD) weekly cholesterol tests performed were 6,361 (682) in 2019 vs. 3,867 (2,373) in 2020 (P = 2.6 × 10−5), representing an overall decline of 39.2%. However, weekly testing rates in 2020 were not uniform. Greatest reductions coincided with the "first wave" of the pandemic (March-May 2020), with up to 92% reductions in testing observed. In the first 14 weeks of each study period (March to mid-June), weekly testing rates were 71.8% lower in 2020. Among individuals tested in 2020, those tested between March and mid-June had substantially lower total cholesterol compared with individuals tested after mid-June (174.2 vs. 181.5 mg/dL, P<2.2 × 10−16). Conclusions: In a large integrated healthcare system, cholesterol testing rates were 39% lower between March-September 2020 compared with the same time period in 2019. Mechanisms for safely facilitating cholesterol testing and management for high-risk patients will be important as COVID-19 re-surges across the U.S. until widespread vaccination and population immunity allow resumption of routine preventive care.